2015
DOI: 10.1007/s11431-015-5772-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of failure mode in geometrically imperfect DP590 steel

Abstract: Various microstructure-level finite element models were generated according to the real microstructure of DP590 steel to capture the mechanical behavior and fracture mode. The failure mode of the dual-phase (DP) steels, mainly resulting from microstructure-level inhomogeneity and initial geometrical imperfection, was predicted using the plastic strain localization theory. In addition, dog-bone-type tensile test specimens with different edge qualities were prepared and the deformation processes were recorded us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Additionally, a dislocation based strain hardening approach [7] was applied to model single phase flow curve in former studies using RVE technique. The model with parameters according to Zhuang et al [6] and the flow curve are shown in Fig. 2.…”
Section: Micromechanical Modeling Of Dp780 Steelmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a dislocation based strain hardening approach [7] was applied to model single phase flow curve in former studies using RVE technique. The model with parameters according to Zhuang et al [6] and the flow curve are shown in Fig. 2.…”
Section: Micromechanical Modeling Of Dp780 Steelmentioning
confidence: 99%
“…However, including the mentioned researches, the concentration is mainly placed on the mechanism of failure mode induced by the heterogeneous microstructure, without considering deformation history of previous process. An investigation has been made with a geometrically imperfect DP590 steel by Zhuang et al [6]. The imperfection was ingrained on the edge of RVE model, which was assumed as a consequence of previous process.…”
Section: Introductionmentioning
confidence: 99%